OPPORTUNITIES TO PROVIDE EMPLOYMENT AND REDUCE POVERTY IN NEIGHBORHOODS (European Journal of Economics, Finance and Business Development, 2024)
The article presents the concept of poverty, the world situation in this regard, as well as the results of research analysis on the possibilities of providing employment in neighborhoods and reducing poverty.